Modul Membaca Kritis Teks Laporan Hasil Observasi untuk Siswa Kelas VII - Sutriono Hariadi; Muakibatul Hasanah; Wahyudi Siswanto (Pascasarjana Universitas Negeri Malang, 2018)
In general, this study aims to produce a critical reading module for grade VII students. Specifically, this study aims to (1) produce a critical reading module of observational report text for grade VII students and (2) test the effectiveness of the module to improve students' critical reading skills. The development procedure used refers to the 4D Model consisting of four stages of development. First, the defining phase includes initial analysis, student and teacher analysis, theoretical study by conducting reference studies, and objective analysis by formulating indicators of critical reading skill aspects developed. Second, the design stage is the collection of text, text processing, presenting the material in accordance with the established structure, and making supporting illustrations. Third, the development stage is done module improvement with product test, revision, and test of effectiveness in the field. Fourth, the dissemination stage is done module printing and sharing of research results in the MGMP forum. Expert and practitioner test results indicate that the product is suitable for use as a critical reading model of LHO text from content, presentation, language, and graffiti aspects. Field test results indicate the product is effective to improve students' critical reading ability. Secara umum, penelitian ini bertujuan untuk menghasilkan modul membaca kritis untuk siswa kelas VII. Secara khusus, penelitian ini bertujuan untuk (1) menghasilkan modul membaca kritis teks laporan hasil observasi untuk siswa kelas VII dan (2) menguji keefektifan modul tersebut untuk meningkatkan keterampilan membaca kritis siswa. Prosedur pengembangan yang digunakan mengacu Model 4D yang terdiri atas empat tahap pengembangan. Pertama, tahap pendefinisian mencakup analisis awal, analisis siswa dan guru, telaah teori dengan melakukan kajian referensi, dan analisis tujuan dengan merumuskan indikator aspek keterampilan membaca kritis yang dikembangkan. Kedua, tahap perancangan dilakukan pengumpulan teks, pengolahan teks, penyajian materi sesuai struktur yang telah ditetapkan, dan pembuatan ilustrasi pendukung. Ketiga, tahap pengembangan dilakukan penyempurnaan modul dengan uji produk, revisi, dan uji keefektifan di lapangan. Keempat, tahap penyebarluasan dilakukan pencetakan modul dan berbagi hasil penelitian dalam forum MGMP. Hasil uji ahli dan praktisi menyatakan produk tersebut layak digunakan sebagai model membaca kritis teks LHO baik dari aspek isi, penyajian, bahasa, dan kegrafikaan. Hasil uji lapangan menyatakan produk tersebut efektif untuk meningkatkan kemampuan membaca kritis siswa.